Tropical and subtropical dendrochronology: Approaches, applications, and prospects - Quesada Román, Adolfo (2022)
Tropical and subtropical forests cover only 7 % of the Earth’s land surface. Yet, they host nearly half of global tree density with a high species number (~40,000 species), store up to 25 % of global terrestrial carbon and represent one-third of net primary productivity on Earth. Over the last four decades, the study of tree growth in the tropics has gained substantial momentum, not least because of the increasing application in tropical and subtropical climatology, ecology, geomorphology, and archaeology. So far, various tropical and subtropical species have been shown to form growth rings with a regular, sometimes annual, layering that is driven by the species’ sensitivity to climatic, ecological, or geodynamic variations. Here, we provide a detailed review of dendrochronology studies in the tropics indicating their (i) tree growth patterns, (ii) most common regions that have been studied preferentially and the families and genera of trees that have been employed most frequently, so as to provide an overview on the most suitable species, (iii) common approaches and techniques used in tropical and subtropical dendrochronology, (iv) different applications, and (v) limitations inherent to tree-ring research in the tropics. The paper concludes with a call for further research in this still understudied environment and provides potential perspectives for future work in the most biodiverse region of the world.